A flexible strain sensor based on conductive TPU/CNTs‐Gr composites. Issue 27 (30th April 2022) - Zhang, Yajie; Li, Chenchen; Zhou, Bangze; He, Haotian; Zhou, Yanfen; Jiang, Liang; Zhou, Feng‐Lei; Chen, Shaojuan
Abstract: A flexible strain sensor with excellent mechanical and electrical properties was fabricated by depositing carboxylated multiwalled carbon nanotubes (CNTs) and graphene (Gr) onto thermoplastic polyurethane (TPU) nanofibrous membranes. The deposition efficiency and fastness of CNTs and Gr particles on TPU nanofibrous membranes were improved by vacuum assisted deposition and ultrasonication. Furthermore, a flexible strain sensor with excellent sensing performance was obtained by optimizing the optimal hybrid ratio between CNTs and Gr. Electromechanical experiments showed that the strain sensor had a wide working range of 172% with a high‐gauge factor of approximately 217 for TPU/5CNTs5Gr composite. Moreover, the TPU/5CNTs5Gr composite also exhibited good durability in 10, 000 tensile loading‐unloading cycles, and had superior sensing performance when monitoring the bending motions of human finger, elbow and knee. Abstract :